Problematika Rumah Tangga Pemburu di Kecamatan Lintau Buo - Risma, Wahyuni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Lintau Buo sub-district there are many men who like to hunt. The hunter's habit of keeping dogs makes him neglect family interests. This caused household problems in the hunter's family in Lintau Buo Sub-district and ended in divorce. The purpose of this study was to determine the objective conditions of the hunters in Lintau Buo Subdistrict, to determine the purpose of the hunters hunting in Lintau Buo District, to find out to find out the effects of the hunting husband on the integrity of the household. This research is a field research. Data collection techniques through observation, interviews, and documentation. To analyze data, the authors use data reduction, data display, and conclusions or verification. The results of this study state that: First, based on objective conditions there are 40% of 9,460 men who like to hunt. They consisted of 3,647 children and adults. They hunt are influenced by curiosity, offspring, the influence of friends and the environment. Second, the purpose of hunting poachers in the Lintau Buo District is to socialize in the community, entertainment and sports facilities, self-satisfaction, grow the economy, and eradicate pests. Their dominant goal is hunting for self-satisfaction. This can be seen from the behavior of hunters who prefer dogs over family. Third, hunting has a negative effect on hunter's worship, one of which ignores worship. Then it has an impact on the household, because the hunter's behavior in hunting creates disharmony that can end in divorce. It was noted that from 2016-2018 there were 88 couples from families of divorced hunters and 30 people had not arranged divorce to the religious court. Another consequence for the community is to keep hunting dogs unconcerned with the cleanliness of their environment. In addition, this results in lowering the hobbies to children, and disrupting the educational process of children because they do not go to school